Naaladiyar : in english version with commentary - Arangasamy, P. (Thanjavur : Muttamil Nilayam, 2020)
Tamil poetic work of didactic nature belonging to the Pathinenkilkanakku anthology of Tamil literature, contains 400 poems, each containing four lines. Every poem deals with morals and ethics, extolling righteous behaviour. Naaladiyar was composed by Jain monks.
Keywords: Tamil literature